2018
DOI: 10.1111/famp.12370
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Self and Dyadic Adjustment in Couple Relationships: A Dyadic Analysis Using the Actor‐Partner Interdependence Model

Abstract: Bowen's multigenerational theory provides an account of how the internalization of experiences within the family of origin promotes development of the ability to maintain a distinct self whilst also making intimate connections with others. Differentiated people can maintain their I-position in intimate relationships. They can remain calm in conflictual relationships, resolve relational problems effectively, and reach compromises. Fusion with others, emotional cut-off, and emotional reactivity instead are commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 53 publications
5
23
0
6
Order By: Relevance
“…Our data revealed that EC and FO have strong clinical relevance and encourage therapists to routinely assess the levels of differentiation of self in individuals, partners, or family members where anxiety and panic problems exist (Lampis, Cataudella, Agus, Busonera, & Skowron, 2019). These screenings could facilitate individual, couples, or family counseling in several ways (Skowron, 2000; Timm & Keiley, 2011).…”
Section: Discussionmentioning
confidence: 80%
“…Our data revealed that EC and FO have strong clinical relevance and encourage therapists to routinely assess the levels of differentiation of self in individuals, partners, or family members where anxiety and panic problems exist (Lampis, Cataudella, Agus, Busonera, & Skowron, 2019). These screenings could facilitate individual, couples, or family counseling in several ways (Skowron, 2000; Timm & Keiley, 2011).…”
Section: Discussionmentioning
confidence: 80%
“…Bowen posited that the influence of differentiation on intimacy and romantic relationships is universally applicable (Kerr & Bowen, 1988). Prior research on BFST in the United States has suggested that a positive relationship exists between DoS and couple adjustment (Knerr & Bartle‐Haring, 2010; Skowron, 2000), and empirical findings from several countries substantiate this claim (e.g., Korea, Italy, Spain, see Chung & Gale, 2006; Lampis, Cataudella, Agus, Busonera, & Skowron, 2018; Rodríguez‐González, Skowron, Cagigal, & Muñoz, 2016). These studies across multiple cultural groups and nations outside of the United States show there is an increasing interest in cross‐cultural applications of BFST by researchers and clinicians.…”
Section: Theoretical Backgroundmentioning
confidence: 95%
“…Different studies conducted in Western countries have revealed that well‐differentiated individuals enjoy good physical and psychological health (Jankowsky, Hooper, Sandage, & Hannah, ; Lampis, Cataudella, Busonera, & Skowron, 2017b; Rodriguez‐Gonzalez et al., ; Skowron, Stanley, & Shapiro, ), are less anxious (Skowron et al., ), and have good levels of psychosocial, relational, and social adjustment (Burri, Schweitzer, & O'Brien, ; Lampis, ; Lampis et al., ; Lampis, Cataudella, Busonera, & Skowron, 2017a; Rodríguez‐González, Skowron, Cagigal de Gregorio & Muñoz San Roque, ; Skowron, ).…”
Section: Bowen Family Systems Theorymentioning
confidence: 99%